The impact of dementia and other comorbidities on increased risk of subsequent hip fracture following hip fracture in Australia: a competing risk approach. (2017) - Harvey, Lara; Mitchell, Rebecca; Brodaty, Henry; Draper, Brian; Close, Jacqueline
No abstract available